Perception of Nursing Student about Integrating Standardized Nursing Language into the Nursing Curriculum at Two Nigerian Universities - Iyanuoluwa Oreofe Ojo; Prisca Olabisi Adejumo; A.A.E. Olaogun; Olufemi O. Oyediran (Elsevier, 2020)
Standardised nursing language is needed in contemporary nursing practice and education to plan, deliver and communicate the contribution of professional nursing practice to other nurses, health care providers, and health consumers. This study assessed the perception of the nursing students about integrating standardised nursing language (SNL) into the nursing curriculum; nursing students' awareness of the SNL, differences between the institution of the participants and their perception; as well as differences between the institution of the participants and their level of awareness about SNL. A cross-sectional research design was adopted. The participants were recruited by using the convenience sampling technique. Data were collected via self-structured questionnaires whose validity and reliability had been previously ascertained. The data collected were analysed, using the Statistical Package for Social Sciences (SPSS), version 20.0. Results showed that the majority of the nursing students that participated in the study were female (86.7%). Also, the majority (74.2%) were aware of SNL. While 58% had a very good perception that SNL is important and should be offered as part of their course system in the institution, only 60.6%, 13.3%, and 11.0% believed it should be offered at undergraduate, postgraduate, and other courses respectively. Further, there was no significant difference in the respondents' institution and their perception while the respondents and their level of awareness were statistically significant, respectively.